PENGARUH STRESSOR TERHADAP STRESS AKADEMIK DAN DAMPAKNYA PADA PENCAPAIAN INDEX PRESTASI DALAM PEMBELAJARAN KURIKULUM BERBASIS KOMPETENSI MAHASISWA KEPERAWATAN STIKES DR. SOEBANDI JEMBER - Ahmad Efrizal Ammrullah; Toni Herlambang; Yusron Rozzadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2016)
Lecture proccess to STIKES dr. Soebandi nursing students since the academic year 2013/2014 using competency-based curriculum where students should be able to reach the target of at least 3.00 of Performance Index. Preliminary studies showed a decrease in the achievement of PI for 3 semesters of lectures caused stressors experienced by students, among others: self ability, finance, security, comfort, college expenses, lectures time, coursework, learning methods, evaluation methods and infrastructure. The purpose of this study was to analyze the effect of stressors on the academic stress and its impact on the achievement of PI. The study design used is non-experimental design with a descriptive, where the cross-sectional approach. It was held on May to July 2015 and located in STIKES dr. Soebandi Jember. Sample was taken by used Non-Probability Sampling with 132 respondents. Analysis of data using test instruments, classic assumption test, path analysis, and t test to test the hypothesis. The test results showed the instrument is valid to r-count < 0.05 and reliable on the value of alpha > r table (0.900 > 0.70). Classical assumption qualify as Best Linear Unbiased Estimator (BLUE) with Asymp. Sig. (2-tailed) of 804 > 0.70 so that data is normal, there is no multicollinearity with VIF values < 10, while the value of Tolerance < 0.10 or > 10 and there are no heteroskesdastisitas with t table < t. Hypothesis testing showed four variables stressor effect on the incidence of academic stress, namely: self ability, coursework, learning methods and infrastructure to the value t count > t table. T test results showed academic stress variables affect the achievement of the Performance Index with the value t count > t table.From the findings can be put forward several suggestions: 1. The admissions process to be more selective based on ability and academic self sufficient and given a briefing before following the lecture. 2. Provision of the coursework to students in order to adjust to the academic load and bustle of students. 3. Choose the method of learning more precise. 4. Completing the facilities and infrastructure. 5. Further research by adding the object in the variable. 6. Adding the variables that have not been covered in this study